2019
DOI: 10.3390/ijms20174291
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Research on the Role of Flavonoids in Lung Cancer

Abstract: Lung cancer is the leading cause of cancer deaths worldwide. Therefore, for the prevention, diagnosis, prognosis and treatment of lung cancer, efficient preventive strategies and new therapeutic strategies are needed to face these challenges. Natural bioactive compounds and particular flavonoids compounds have been proven to have an important role in lung cancer prevention and of particular interest is the dose used for these studies, to underline the molecular effects and mechanisms at a physiological concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 100 publications
1
51
0
Order By: Relevance
“…By far, the prognosis remains unsatisfactory, despite the availability of traditional treatment options involving surgery, radiation, chemotherapy, and specific targeted therapies, primarily due to late diagnosis and late appearance of metastasis, especially in conditions associated with lung cancer [ 264 , 265 ]. The role of numerous flavonoids in lung cancer have been discussed by Zanoaga et al and Collins et al [ 266 , 267 ], and Qu, identified as having antitumor properties, has been tested for its impact on aurora B activities in a study conducted by Xingyu et al [ 160 ]. Aurora B, a protein part of series of serine–threonine kinase, is important during attachment of mitotic spindle to the cancer cells and centromere; overexpression of aurora B causes uneven division of genetic information, generating aneuploidy in cells, a characteristic of cancer [ 268 ].…”
Section: Role Of Qu In Prevention and Inhibition Of Various Types mentioning
confidence: 99%
“…By far, the prognosis remains unsatisfactory, despite the availability of traditional treatment options involving surgery, radiation, chemotherapy, and specific targeted therapies, primarily due to late diagnosis and late appearance of metastasis, especially in conditions associated with lung cancer [ 264 , 265 ]. The role of numerous flavonoids in lung cancer have been discussed by Zanoaga et al and Collins et al [ 266 , 267 ], and Qu, identified as having antitumor properties, has been tested for its impact on aurora B activities in a study conducted by Xingyu et al [ 160 ]. Aurora B, a protein part of series of serine–threonine kinase, is important during attachment of mitotic spindle to the cancer cells and centromere; overexpression of aurora B causes uneven division of genetic information, generating aneuploidy in cells, a characteristic of cancer [ 268 ].…”
Section: Role Of Qu In Prevention and Inhibition Of Various Types mentioning
confidence: 99%
“…The 5-year survival rate of patients with lung cancer is <17% ( 6 ). Different anticancer strategies have been developed and used in clinical treatment of lung cancer, including surgery, chemotherapy, immunotherapy and targeted therapy ( 10 13 ). However, these strategies do not effectively improve the long-term survival rate of patients with lung cancer, so novel effective therapeutic interventions and targets are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products can regulate melanogenesis through AhR activation [ 23 ]. AS-IV is a kind of natural flavonoids [ 24 26 ] which have been identified as exogenous ligands of AhR [ 27 ]. Currently, our study showed that AS-IV could stimulate the melanin synthesis via activating AhR in NHEMs.…”
Section: Discussionmentioning
confidence: 99%